Influence of Different Drinks on the Colour Stability of Dental Resin Composites - Topcu, Fulya Toksoy; Sahinkesen, Gunes; Yamanel, Kivanc; Erdemir, Ugur; Oktay, Elif Aybala; Ersahan, Seyda (European Journal of Dentistry, 2009)
Objectives: The objective of this study was to evaluate the discolouration effects of artificial saliva, granule lemon juice, coffee (without sugar), coca cola, sour cherry juice, fresh carrot juice and red wine on resin-based composite materials that are commonly used in restorative dentistry.Methods: Colour of four brands of resin composites (Filtek Z 250 (3M Espe), Filtek Supreme (3M Espe), Quadrant (Cavex), Charisma (Heraeus-Kulzer)) of A2 shade was measured after one day of immersion in eight different solutions. Colour measurements were obtained by using a XL-20 Trismus Colourimeter and colour differences (E) were estimated. For statistical evaluation, analysis of variance (ANOVA), Dunnett and Tukey tests were used at a significance level of 0.05.Results: For the four restorative materials tested, the lowest ΔE values were observed in the artificial saliva, while ΔE values were the highest in red wine group. When comparing the four different restorative materials, Filtek Supreme exhibited the least colour changes whereas Filtek Z250 was the least colour-stable.Conclusions: Dental resin composites and drinking solutions were significant factors that may affect the colour stability. After immersion for one day, all materials showed visible colour changes. The red wine solution exhibited more staining than others in three groups. Filtek Supreme showed significantly the least colour change due to its nano particle sizes. (Eur J Dent 2009;3:50-56)
Keywords: Colour; Composite; Drink